Chemical tools to track and perturb the expression of sialic acid and fucose monosaccharides. Issue 87 (12th October 2022) - Rossing, Emiel; Pijnenborg, Johan F. A.; Boltje, Thomas J.
Abstract : The biosynthesis of glycans is a highly conserved biological process and found in all domains of life. Metabolic glycomimetics enable us to visualize and perturb these processes and the functions of the glycan products. Abstract : The biosynthesis of glycans is a highly conserved biological process and found in all domains of life. The expression of cell surface glycans is increasingly recognized as a target for therapeutic intervention given the role of glycans in major pathologies such as cancer and microbial infection. Herein, we summarize our contributions to the development of unnatural monosaccharide derivatives to infiltrate and alter the expression of both mammalian and bacterial glycans and their therapeutic application.